المراجعة بالعينات الإحصائية في عمل المراجع الخارجي دراسة ميدانية (الجهاز المركزي للرقابة المالية) في الجمهورية العربية السورية - الدغيم عبد العزيز; الأمين ماهر; الحاطوم لقمان حمدان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نظراً لاتساع حجم العمليات المحاسبية وزيادة تشابكها وتعقيدها تزداد الحاجة إلى أسلوب المراجعة الاختبارية والذي يعتمد على اختيار عينات من العمليات المحاسبية ومراجعتها وتدقيقها لاكتشاف الأخطاء وتقويمها وتحديد المسؤولية عنها بدقة وبزمن وتكلفة أقل. وقد ركز الباحث على مفهوم المراجعة الاختبارية ومدى تطبيقها في سورية وأعد لذلك استبياناً من /190/نسخة تم توزيعها على مفتشين من الجهاز المركزي للرقابة المالية والذين تبين أنهم من خلال تحليل النتائج يقومون باستخدام أساليب المراجعة الاختبارية التي تعد أساس العمل الميداني للمراجع الخارجي في وقتنا الحاضر مع ملاحظة نقص في الخبرات باستخدام الأساليب الإحصائية وعدم وجود معايير مراجعة تشكل أساس عمل مفتشي الجهاز. Due to the expansion of the volume of accounting operations and its increased complexity, the Audit Sampling method becomes more necessary, which depends on selecting samples of the accounting operations, detecting errors , correcting them, and accurately determining the responsibility in time- and cost-efficient way. The study has focused on the concept of Audit Sampling and the extent of its application in Syria. A questionnaire of 190 copies has been prepared for that purpose, which was distributed to the inspectors of the (the Central Body of Financial Control ) who proved through the analysis of the results that they were employing the methods of Audit Sampling, which are considered the bases of fieldwork for the external auditors at present, noticing the lack of experience regarding the application of statistical methods along with lacking auditing standards that form the activity bases of the body inspectors.